Benefit of a more extended pelvic lymph node dissection among patients undergoing radical prostatectomy for localized prostate cancer: A causal mediation analysis. Issue 5 (18th February 2021) - Wettstein, Marian S.; David, Luke A.; Pazhepurackel, Clinsy; Qureshi, Aatif A.; Zisman, Alex; Nesbitt, Michael; Saba, Karim; Herrera‐Caceres, Jaime O.; Fankhauser, Christian D.; Ahmad, Ardalan; Hamilton, Robert J.; Eberli, Daniel; et al.
Abstract: Background: The therapeutic role of extended (ePLND) versus nonextended pelvic lymph node dissection (nePLND) to remove occult micrometastases in men undergoing radical prostatectomy for localized prostate cancer (PC) is conflicting. Therefore, our aim was to quantify the direct effect of ePLND versus nePLND (removal of occult micrometastases), which is not mediated through the detection of nodal disease and potential adjuvant therapy (indirect effect). Methods: Retrospective, bi‐center cohort study of consecutive patients undergoing radical prostatectomy and PLND for PC (January 2006 and December 2016). Patients were followed until April 2018 for the occurrence of either biochemical recurrence or secondary therapy (composite outcome). ePLND was compared to nePLND by unweighted and weighted survival analysis (total effect) as well as by causal mediation analysis (direct and indirect effect). Results: Positive nodal disease was detected in 71 (7%) out of 1008 patients undergoing radical prostatectomy and PLND for PC (ePLND: 368 [36.5%]; nePLND: 640 [63.5%]). Survival analysis demonstrated results in favor of ePLND (unweighted hazard ratio: 0.77 [95% confidence interval: 0.59–1.01], p = .056; weighted hazard ratio: 0.75 [0.56–0.99], p = .044). The causal mediation analysis confirmed the total effect of 0.77 (0.71–0.82). After disentangling this total effect into an indirect effect (via detection of nodal disease and potential adjuvant therapy) and a direct effect (via removal of occult micrometastases), we identified an even more protective direct effect of 0.69 (0.63–0.75). Conclusions: Our results not only indicate the utility of ePLND but also that its impact is not restricted to a staging benefit and probably involves a therapeutic benefit mediated through the removal of occult micrometastases.